The PGPR Fertilizer Processing Training in Banyuresmi Village, Jiput District, Pandeglang Regency, Banten Province - Muhamad Fakhrudin; Elif Pardiansyah; Bagus Dwi Cahyono (MOVE: Journal of Community Service and Engagement, 2022)
The availability of organic fertilizer is one of the keys to the success of the go-organic program that is scheduled by the government. Increasing the use of organic fertilizers and reducing the use of pesticide fertilizers, it is expected to increase the yield of bamboo farming in Banyuresmi Village. Plant Growth Promoting Rhizobacteria (PGPR) fertilizer is one way to restore soil fertility because some bacteria from the PGPR group are nitrogen-fixing bacteria. Thus, it is necessary to socialize and assist the manufacture of PGPR fertilizer in Banyuresmi Village. The method of implementing this activity includes 1) the preparation stage, namely preparing a simple guide, and preparing tools and materials for the manufacture of mycorrhizal-PGPR combination. 2) the implementation stage consists of a) (Lecture/Counseling Method); b) Training for the manufacture of mycorrhizal-PGPR combinations; Discussion and question and answer; and Evaluation. This training concludes that the residents of Banyuresmi Village are greatly helped by the training in making PGPR fertilizer. Through the training, the residents of Bnyuresmi Village received information about processing PGPR fertilizer as a way to increase the production of bamboo plant commodities.